Evangelical Theology, Biblical Archaeology and American Schools of Oriental Research’s continuing relevance - Arbino, Gary P. (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
The relationship between theologically-centered biblical studies and archaeology has not always been smooth and American Schools of Oriental Research (ASOR) has often been involved in the debates. While methodological solutions have been regularly discussed, the theological impulses that give rise to the specific readings that archaeologists and historians find so very troubling have received little attention. This paper seeks to make a small contribution to that deficit by articulating the twin theological commitments of Authority and Inspiration and how these shape the conversation from the perspectives of Evangelicals and those utilizing Theological Interpretation. Five modest suggestions for archaeologists’ engagement with those theologically committed are offered.